The Property of Language: Norm and Usage in the work of Ricardo Monner Sans (Anclajes, 2018)
The question of purity in language has been a common topic in the fields of language ideological debates in the Spanish-speaking world. In this paper, we propose an analysis of the various conceptualizations on linguistic correctness in the work of Ricardo Monner Sans in order to elucidate the links between his linguistic theory and his position on language policy. In that sense, we assume that these conceptualizations should be analyzed as a consequence of a more general consideration about linguistic usage and purity. This consideration seeks a regulatory intervention on the linguistic practices of society based on philological knowledge. Thus, the dimension of usage is divided into a common usage which corresponds to the widespread use in community, and correct usage, that which has been legislated by philological knowledge and which is, for this reason, the criteria for linguistic correction on which the ideal of a homogeneous linguistic community is based.
Keywords: Ricardo Monner Sans; Linguistics historiography; Language-ideological debates; 19th and early 20th century; Argentine